Synthesis of Silver and Zinc Oxide Nanoparticles Using Polystichum lentum Extract for the Potential Antibacterial, Antioxidant, and Anticancer Activities - Deepak Kumar Shrestha; Akash Budha Magar; Manisha Bhusal; Rabina Baraili; Ishwor Pathak; Pusp Raj Joshi; Niranjan Parajuli; Khaga Raj Sharma (Journal of Chemistry)
The present research involves a green synthesis of silver and zinc oxide nanoparticles using an aqueous extract of Polystichum lentum and a comparison of bioactivities. Phenolics, flavonoids, alkaloids, steroids, and saponins were present in the aqueous extract. The highest TPC and TFC were found in ethanol extract with 124.93 ± 9.36 mg GAE/g and 28.73 ± 1.98 mg QE/g. The formation of Ag and ZnO NPs was confirmed by the appearance of peaks at 421 nm and 362 nm in UV-visible spectra. The involvement of plant secondary metabolites in nanoparticle synthesis was indicated by the shifts in peak positions and peak intensities in FTIR spectra. SEM and XRD analyses established spherical morphology (average size 61.33 ± 15.31 nm) and FCC crystal structure for Ag NPs and hexagonal to round morphology (average size 97.20 ± 12.92 nm) and hexagonal wurtzite crystal structure for ZnO NPs. EDX analysis revealed the elemental composition of nanoparticles. The IC50 values of 51.95 ± 3.11 and 83.79 ± 6.63 μg/mL for Ag NPs and ZnO NPs in the DPPH assay were significantly higher than 32.07 ± 1.03 and 6.53 ± 1.57 μg/mL for aqueous and methanol extracts. ZnO nanoparticles showed comparatively higher ZOI of 14 and 16 mm against Shigella sonnei and Klebsiella pneumoniae. It also displayed the lowest MIC and MBC of 3.125 and 6.25 mg/mL against Staphylococcus aureus and Klebsiella pneumoniae. The nanoparticles also exhibit potent cytotoxicity with IC50 of 76.82 ± 1.67 μg/mL against cervical cancer cell lines. Both nanoparticles and aqueous extract were mildly toxic towards the brine shrimp nauplii with the lowest LC50 being 661.80 ± 64.21 μg/mL for the aqueous extract. In conclusion, the findings of the present study demonstrate the high antioxidant, antibacterial, and anticancer activities in Ag and ZnO nanoparticles synthesized using an aqueous extract of Polystichum lentum.